Implementasi Program Asuhan Mandiri Toga di Puskesmas Sawit: Seberapa Penting Dukungan Lintas Sektor dan Masyarakat? - Fitriana Fatika Khaerani; Dwi Linna Surwardany (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
One of the health services that can improve the quality of life and welfare of the community is the traditional health service program. Traditional health services are treatments in a way that is based on experience and hereditary skills. One of the types of traditional health services that are developing is the family medicinal plants garden (TOGA). This study aims to analyse and describe the implementation of the TOGA Self-Care program at the Sawit Health Center Boyolali. The type of research used in this study was qualitative research with a Case Study approach. The type of interview is a semi-structured interview with an average vulnerable interview time of about 45 minutes. This study interviewed 8 research subjects, namely the manager of the traditional health program of the Boyolali Regency Health Office, the Head of the Sawit Health Center, the person in charge of traditional health services of the Sawit Health Center, Asman TOGA Cadres, and the community who participated in the Asman TOGA Program. The study results show that the TOGA Self-Care Program in Boyolali Regency has been running effectively with strong regulatory support and active community participation, which is marked by the formation of the Asman TOGA group in each Posyandu. However, there are still obstacles such as limited cadre time, lack of funds, and problems with irrigation and plant care, so it is necessary to increase community empowerment and cross-sector cooperation to ensure the program's sustainability.